Fake Sacred Tomb Business in The Coastal Areas of West Kalimantan in The Era of Regional Autonomy - Abu Bakar; Hakimah, Nur; Hudi Prasojo, Zaenuddin; bin Haji Masri, Sahrin (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
In the coastal areas of West Kalimantan, several new sacred tombs have recently become the subject of community discussions, first emerging around 2020. This study seeks to uncover the existence of these tombs and reveal the underlying facts so that the true events can be accurately explained. To achieve this, the study employed qualitative methods and a phenomenological perspective to address the research focus. Data were collected through observations at the research sites and interviews with relevant stakeholders. All data were validated using member-checking techniques to ensure accuracy and credibility. Subsequently, the data were analyzed in detail, developing concepts that explain the actual events. The study’s findings indicate that business activities drive the emergence of these new sacred tombs. Among the tombs identified are the tomb of Hasan in Pontianak, Muhammad in Kubu Raya, Usman in Mempawah, and the Nine Sacred Tombs in Ketapang. These tombs have been established based on the claims of individuals who assert their origin from dreams and/or supernatural events rather than from historical evidence. The analysis suggests that the context of Regional Autonomy plays a significant role, as it reflects a policy trend of developing sacred tombs for pilgrimage into religious tourism aimed at boosting the regional economy. This policy has seemingly inspired the creation of fake sacred tombs, which copy well-known tombs that are centers of religious tourism. The business activities surrounding these fraudulent tombs include selecting tomb sites, socialization, promotion, site management, and the economic benefits of pilgrim donations. The phenomenon of new sacred tombs is not unique to West Kalimantan but is also observed in other regions of Indonesia. Given the scope of this trend, further research is needed to provide a comprehensive explanation of the emergence of these new sacred tombs to enlighten the community.